Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1023/a:1008276632623
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and sequelae in patients treated with brachytherapy and external beam irradiation for localized prostate cancer

Abstract: The study demonstrates that survivors from localized prostate cancer treated with an association of BT and EBI have good global health status. Major problems that persist are sexual disorders, urinary incontinence and cystitis while digestive disorders were rare. This association could be an alternative to standard EBI in patients with localized prostate cancer. Whatever the treatment choice, patients should be involved in the therapeutic decision which should consider not only expected survival rate but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…Similar findings with no difference in QOL also were reported by Lilleby et al 14 and by Joly et al 15 comparing patients treated with brachytherapy and external irradiation with controls. Two Scandinavian population studies 17,25 showed the same magnitude of QOL in the age group of men older than 70 years as in the control group in the current study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings with no difference in QOL also were reported by Lilleby et al 14 and by Joly et al 15 comparing patients treated with brachytherapy and external irradiation with controls. Two Scandinavian population studies 17,25 showed the same magnitude of QOL in the age group of men older than 70 years as in the control group in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…A similar level of reported urinary problems also was found in an earlier study comparing PC patients and controls. 8 Joly et al 15 also showed that incontinence was one factor that differed between the patients and controls and was reported more often as a problem by the patients than by physicians.…”
Section: Discussionmentioning
confidence: 97%
“…[11][12][13] Instead of developing an instrument de novo based on input from prostate cancer survivors, Talcott and Clark constructed a questionnaire combining items adopted from various prior non-validated prostate cancer surveys with items constructed based on practitioner input. Their consequent "Symptom Index" has 29 items and was validated for quantifiable measurement of urinary, bowel, and sexual domains, with the ability to distinguish function and distress (Table 1).…”
Section: Validated Questionnaires: Instruments To Measure Hrqolmentioning
confidence: 99%
“…[12] The EORTC Genito-urinary group developed a 12-item module for evaluating prostate cancerrelated HRQOL in conjunction with the QLQ-C30 (Table 1). [13] This module included evaluation of urinary, bowel, and sexual domains; however, despite querying urinary irritative symptoms as well as urinary incontinence, the module was not designed to specifically measure the irritative and incontinence concerns as separate domains, and instead provides only a urinary summary score. A potential limitation of such a summary score is that discordant incontinence versus obstruction symptoms can be difficult to detect and evaluate.…”
Section: Validated Questionnaires: Instruments To Measure Hrqolmentioning
confidence: 99%
“…11 For men with prostate carcinoma, the incontinence and impotence that follow most treatment modalities cause the most distress and significantly compromise quality of life. [12][13][14][15][16][17] Whereas urinary control and sexual function are worse after surgery, bowel dysfunction is common after radiation therapy. 18,19 Patients report high rates of dysfunction after receiving treatment for early-stage prostate carcinoma and are surprised by the intensity and duration of treatment side effects, which play a major role in limiting physical functioning.…”
mentioning
confidence: 99%